2018
DOI: 10.14710/agrisocionomics.v2i1.3137
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Lama Melaut, Kekuatan Mesin Tempel, Dan Karakteristik Responden Terhadap Pendapatan Nelayan Tangkap Tradisional Di Kabupaten Takalar

Abstract: Perubahan musim di Perairan Selat Makassar yang berbatasan langsung dengan wilayah pesisir pantai Barat Kabupaten Takalar mengakibatkan perubahan jumlah tangkapan sehingga berdampak pada pendapatan usaha tangkapnya. Penelitian ini bertujuan menganalisis pengaruh lama melaut, kekuatan mesin tempel, karakteristik respoden terhadap pendapatan nelayan tangkap. Analisis data menggunakan Ordiary Least Square (OLS) dari data cross-section yang bersumber dari data primer Tahun 2016. Hasil penelitian menunjukkan bahwa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
3
0
5
Order By: Relevance
“…This result is in line with research [14] which revealed that age has a negative effect on the welfare of traditional fishermen. The experience of fishermen has no effect on the income of traditional fishing fishermen in Takalar Regency [15].…”
Section: Factors Affecting the Level Of Welfare Of Crab Fisherman's H...mentioning
confidence: 96%
“…This result is in line with research [14] which revealed that age has a negative effect on the welfare of traditional fishermen. The experience of fishermen has no effect on the income of traditional fishing fishermen in Takalar Regency [15].…”
Section: Factors Affecting the Level Of Welfare Of Crab Fisherman's H...mentioning
confidence: 96%
“…Hasil penelitian Sari, et al, (2017) menunjukkan bahwa tingkat pendidikan tidak berpengaruh nyata tehadap kesejahteraan keluarga nelayan mini purse seine. Begitu pula dari kajian Rahim et al, (2018). Pendidikan tidak berpengaruh terhadap pendapatan nelayan tangkap di Desa Galesong Kota Kecamatan Galesong Kabupaten Takalar dan hasil penelitian Husni et al, (2021), tingkat Pendidikan nelayan rajungan tidak berpengaruh nyata terhadap tingkat kesejahteraan nelayan.…”
Section: Tabel 3 Uji Ketepatan Model Dari Nilai Runclassified
“…Most of them were from the Sundanese ethnic group and as many as 49 respondents and junior high school graduates dominated the educational level of the workers. Furthermore, it has been studied that the ability to fish is influenced by the educational level of a worker [16]. Only a few of the workers in the Limau Sub-district had second jobs and they include laboring (buruh), small-time entrepreneurship and farming.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%